The Effects of Νatural Enemies on Aphid Populations on Processing Tomato in Central Greece - Lykouressis, Ρ.; Perdikis, D. CH.; Chalkia, CH. Α. (ENTOMOLOGIA HELLENICA, 2000)
Two species of aphids, Macrosiphion euphorbiae (Thomas) and Myzus persicae cae (Sulzer) (Homoptera: Aphididae) were the only ones which developed populations on processing tomato in a two year study conducted in central Greece. The aphid population structure showed that M. euphorbiae was much more abundant than M. persicae in both years. The former species peaked in August whilst the latter did not show any particular peak over the two successive years. Some species of natural enemies were recorded. Orius niger Wolff was found in low numbers scattered over a long period but mainly towards the end of the growing season, and it did not correlate with the aphid population. The rate of parasitism of M. euphorbiae by Aphelinus abdominalis Dalman and Praon volucre (Haliday) was very low and it seemed that these two parasitoid species did not have any particular effect on the aphid population suppression. Macrolophus pygmaeus Rambur was the key natural enemy and the most abundant and effective among the predators found. Its highest numbers occurred towards the end of the growing season following the aphid population peak, suggesting a numerical response of this species to its prey. A proportion of the population of M. pygmaeus occurring on tomato plants after fruit harvesting, might he collected and subsequently released in crops such as tomato, pepper and eggplant to biologically control pests in greenhouses, like aphids and whiteflies, thus contributing to the production of healthy vegetable products.